The protection of the cross-border credit by the European Account Preservation Order. Regarding the ECJ Judgment C-555/18 Of 7 November of 2019 - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The European Account Preservation Order is a very useful measure that attempts to facilite the collection of cross-border debts. The ECJ judgment of 7 of November of 2019 is the first about the Regulation 655/2014. This Regulation establishes the European precautionary measure in all EU member states with the exception of Denmark. This ruling shows that the application of the European Account Preservation Order may not be easy to apply to national courts. One of the reasons is that its application requires a harmonious combination between the provisions of Regulation 655/2014 and national procedural orders. The ECJ with this judgment that we analyze tries to pave the way towards the search for that harmonious and especially homogeneous application of R. 655/2014 by the national courts of the member states.